PS-038 Appropriateness of new oral anticoagulant prescriptions: analysis of pharmacist interventions. (24th March 2015) - Carmona, P; Agirre, I; Lizeaga, G; Lizardi, A; Bachiller, MP; Andueza, K; Esnaola, E; Aranguren, MA; Leunda, L; Umerez, M
Abstract : Background: New oral anticoagulants are an alternative to acenocoumarol in the prevention of stroke and systemic embolism in adult patients with non-valvular atrial fibrillation. Purpose: To assess the suitability of prescriptions for new oral anticoagulants for those diagnoses, in accordance with criteria established by the health organisation and to analyse pharmaceutical interventions. Material and methods: A prospective, observational and cross-sectional study of all patients admitted to our hospital who were prescribed dabigatran, rivaroxaban or apixaban from 01/02/2014 to 31/08/2014. Electronic medical records and electronic medical prescriptions were used as data sources. Demographics (age, gender), reason for admission, indication for anticoagulation, risk factors for complications such as renal and hepatic failure, concomitant drugs that increase the risk of bleeding (NSAIDs, platelet inhibitors, low molecular weight heparins) and adverse events were collected. In addition, adverse drug-related events avoided were also recorded. Results: 64 patients (36 men) with mean age of 76 years (range 35–95) were included. 24 patients were treated with dabigatran, 38 with rivaroxaban and 2 with apixaban. 4 of these treatments were used as off-label treatments. 8 patients had renal failure and 23 had a risk of major bleeding due to concomitant treatments, mainly NSAIDs. Pharmaceutical interventions were performed in the 8 cases of renal failure because the doses needed adjustment. 14 patients with concomitant drugs that could increase the risk of bleeding were also monitored. 100% of recommendations were accepted by physicians. 2 severe adverse events were recorded: 2 bleeding episodes. Conclusion: 94% of new oral anticoagulant prescriptions met the criteria established by the healthcare organisation. Pharmacists were involved in the optimisation of a third of the treatments, with total acceptance. It would be desirable to extend this activity, individualization of anticoagulant treatment, into primary medical care. Reference: Agencia Española de Medicamentos y Productos Sanitarios. Informe de posicionamiento Terapéutico UT/V4/23122013 No conflict of interest.